Diptera of sanitary importance associated with composting of biosolids in Argentina Dípteros de importancia sanitaria asociados al compostaje de biosólidos en Argentina - Valeria Alejandra Labud; Liliana Graciela Semenas; Francisca Laos (Universidade de São Paulo, 2003)
OBJECTIVE: Odorous compounds produced at the biosolids composting plant in Bariloche (NW Patagonia) attract a variety of insects, mainly belonging to the order Diptera. In order to characterize these flies, collected specimens were taxonomically identified, their community characteristics were described and their sanitary and synanthropic importance and autochthonous or introduced character were determined. METHODS: Sampling was performed from October 1999 until March 2000. Adults were collected using an entomological net, and larvae and puparia were obtained from the composting material and incubated to obtain adults. Richness, abundance and sex ratio were calculated. RESULTS: A total of 9 taxa of Diptera were identified: Sarconesia chlorogaster, Phaenicia sericata, Calliphora vicina, Cochliomya macellaria, Ophyra sp, Muscina stabulans, Musca domestica, Sarcophaga sp and Fannia sp. Specimens of Anthomyiidae, Acaliptratae and one larva of Eristalis tenax were also found. Ophyra sp. was the most abundant taxa. All the captured Diptera belonged to introduced taxa. Most of them are considered to be eusynanthropic and/or hemisynanthropic and have sanitary importance as they may cause myiasis and pseudomyiasis. The high number of females registered and the finding of immature stages indicated that flies can develop their complete life cycle on biosolid composting windrows. CONCLUSIONS: The characterization of flies obtained in this study may be useful for defining locations of urban or semi-urban composting facilities. It also highlights the importance of sanitary precautions at such plants. OBJETIVO: Los compuestos odoríferos producidos en la Planta de Compostaje de Biosólidos de Bariloche (NO Patagonia) atraen diferentes insectos, principalmente moscas (Orden Diptera). Con el objeto de caracterizarlas, se colectaron especímenes que fueron identificados taxonómicamente. Se describieron sus características comunitarias y se determinó su importancia sanitaria y su carácter autóctono o introducido. MÉTODOS: El muestreo se realizó desde octubre de 1999 a marzo de 2000. Los adultos se colectaron utilizando una red entomológica. Las larvas y las pupas, obtenidas de las pilas de compostaje, se incubaron para obtener adultos. Se calcularon riqueza, abundancia y relación de sexos. RESULTADOS: Se identificaron 9 taxones de Diptera: Sarconesia chlorogaster, Phaenicia sericata, Calliphora vicina, Cochliomya macellaria, Ophyra sp, Muscina stabulans, Musca domestica, Sarcophaga sp y Fannia sp. También se capturaron especímenes de Anthomyiidae, Acaliptratae y una larva de Eristalis tenax. Ophyra sp fue el taxón más abundante. Todos los especímenes capturados pertenecieron a taxones introducidos y la mayoría de ellos, son eusinantrópicos y/o hemisinantrótpicos. Además, tienen importancia sanitaria dado que pueden causar myiasis y pseudomyiasis. La cantidad de hembras registrada y el hallazgo de estadios inmaduros indican que estas moscas pueden desarrollar su ciclo completo de vida en las pilas de compostaje. CONCLUSIONES: La caracterización de las moscas encontradas en la Planta de Compostaje de Bariloche puede ser de utilidad para definir la instalación en zonas urbanas o semi-urbanas de este tipo de plantas. Adicionalmente, aporta información sobre aspectos sanitarios en esta clase de emprendimientos.